15N studies of endogenous faecal nitrogen in infants. Issue 1 (January 1974) - Read, Walter W. C.; McLaren, Donald S.; Tchalian, Marie
Abstract : 15 N from labelled yeast protein, fed to marasmic and recovered infants, appeared in the stool shortly after administration and continued to be excreted for 100 hours. Unabsorbed dietary 15 N, which appeared with carmine-marked stools, formed only part of this excretion. Calculations of the endogenous nitrogen content of infant stool agreed closely with those of previous workers. The use of intravenously injected 15 N showed that part of the stool nitrogen was derived from this source. It was excreted as urea, ammonia, and other compounds, and totalled about 2% of the administered urea. The persistence of the 15 N in the stool suggests that it had in part been incorporated into cellular material.